Workplace Incivility among Portuguese Hotel Employees: Is Lack of Respect Burning Them Out? - Nitzsche, Martina; Ribeiro, Luisa; Laneiro, Tito (Journal of Tourism, Sustainability and Well-being, 2018)
Workplace incivility is defined as rude behaviour that violates social norms at work. It has been linked to psychological distress (burnout), mainly in healthcare and educational settings. Burnout is a serious public health concern. Studies addressing the impact of workplace incivility on employee well-being in the hospitality industry are scarce. The primary aim of this study was to examine the relationship between workplace incivility and burnout among hotel employees. Cross-sectional data for 385 Portuguese hotel employees (54% male; Mage = 33.9, SD = 11.3) were analysed using bootstrap regression models. Results revealed that (1) supervisor incivility was significantly more frequent than coworker incivility; (2) supervisor and co-worker incivility were significant positive predictors of emotional exhaustion and cynicism, the core components of burnout; (3) supervisor incivility was the stronger predictor of emotional exhaustion, and co-worker incivility the stronger predictor of cynicism; and (4) severe burnout was highly prevalent in our sample. This study provides insight into the phenomena of workplace incivility and burnout among Portuguese hotel employees. Our results have practical value for management strategies aiming to prevent or reduce burnout, which in turn has the potential to enhance individual, group, customer and organizational outcomes within the hospitality industry.